2017
DOI: 10.1038/s41598-017-02446-0
|View full text |Cite
|
Sign up to set email alerts
|

Experimental, quantum chemical and molecular dynamic simulations studies on the corrosion inhibition of mild steel by some carbazole derivatives

Abstract: Five selected carbazole derivatives, namely carbazole, 3,6-dibromocarbazole, 2-hydroxycarbazole, 1,2,3,4-tetrahydrocarbazole and 9-(2-ethylhexyl)carbazole-3,6-dicarboxaldehyde were investigated for their inhibitive effects on Desulfovibrio vulgaris (D. vulgaris) induced corrosion of mild steel and in 1 M HCl medium using weight loss, potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) techniques. The carbazole derivatives were found to be mixed type inhibitors with predominantly catho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(32 citation statements)
references
References 63 publications
(106 reference statements)
0
32
0
Order By: Relevance
“…Generally, molecules which have higher E HOMO are more easily to donate electrons to the unlled molecular orbital of suitable acceptor molecules with low energy. 21 Previous studies showed that the inhibition efficiency increases with the increasing E HOMO values. 23,26 In contrast, the E LUMO value is related to the capability of a molecule to accept electrons.…”
Section: Quantum Chemical Calculationmentioning
confidence: 96%
See 3 more Smart Citations
“…Generally, molecules which have higher E HOMO are more easily to donate electrons to the unlled molecular orbital of suitable acceptor molecules with low energy. 21 Previous studies showed that the inhibition efficiency increases with the increasing E HOMO values. 23,26 In contrast, the E LUMO value is related to the capability of a molecule to accept electrons.…”
Section: Quantum Chemical Calculationmentioning
confidence: 96%
“…Quantum chemical calculation was performed using Materials Studio 7.0 soware. [19][20][21] The Density Functional Theory (DFT) method, B3LYP, combined with the 6-311G(d,p) basis [22][23][24] set was used in this study. Full geometry optimizations were carried out on carboxylate ions due to the alkaline environment.…”
Section: Quantum Chemical Calculationmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, removal of these mediators might help in mitigating MIC. Other MIC control strategies use surfactants 29 and mixed-type inhibitors carbazole derivatives to inhibit SRB biofilm formation 30 . Ideally, biofilm inhibitors should be applied at the metal surface, and engineered to allow slow release over long periods of time.…”
Section: Sub-lethal Biofilm Treatmentsmentioning
confidence: 99%